Wind from the North: Hul’q’umi’num’ speakers in Saanich - Seward, Ivy (2019)
Among the First Nations peoples are the Coast Salish tribes that live along the shores of the Salish Sea. The Hul’q’umi’num’ and the Sunchathun are members of two of the ten Coast Salish groups and reside on neighboring territories in southwestern Vancouver Island. They speak two different, but closely-related languages. My research studied Hul’q’umi’num’ speakers who live among the Sunchathun, posing the question: do these speakers talk like each other or different from each other? My finding is that there is no uniform dialect, but rather each speaker uses a form of Hul’q’umi’num’ based on their family connections and personal history. Speakers differed in how much influence Sunchathun had on the way they spoke Hul’q’umi’num’—from none to much—depending on various factors including where they were raised and whether they could speak Sunchathun.